Methylation of Ir(III)-tetrazolato complexes: An effective route to modulate the emission outputs and to switch to antimicrobial properties - Fiorini, V.; Zanoni, I.; Zacchini, S.; Costa, A.; Hochkoeppler, A.; Zanotti, V.; Ranieri, Anna; Massi, Massimiliano; Stefan, A.; Stagni, S. (R S C Publications, 2017)
Two neutral cyclometalated Ir(iii)-tetrazolato complexes that differ by variations of the substituents on either the phenylpyridine or the tetrazolate ligand have been converted into the corresponding methylated and cationic analogues. NMR ( 1 H and 13 C) characterization of the Ir(iii) complexes provided the results in agreement with the chemo- and regioselective character of methylation at the N-3 position of the Ir(iii)-coordinated tetrazolato ring. This evidence was further corroborated by the analysis of the molecular structures of the cationic complexes obtained by X-ray diffraction. In view of the photophysical properties, the addition of a methyl moiety to neutral Ir(iii) tetrazolates, which behave as sky-blue or orange phosphors, caused a systematic red shift of their phosphorescence output. The transformation of neutral Ir(iii) tetrazolates into cationic Ir(iii)-tetrazole complexes was screened for any eventual antimicrobial activity in vitro against Gram negative (E. coli) and Gram positive (D. radiodurans) microorganisms. While both kinds of complexes were not active against E. coli, the conversion of the neutral Ir(iii) tetrazolates into the corresponding methylated and cationic Ir(iii)tetrazole derivatives determined the turn-on of a good to excellent antimicrobial activity toward Gram positive Deinococcus radiodurans, a non-pathogenic bacterium that is listed as one of the toughest microorganisms in light of its outstanding resistance to radiation and oxidative stress.